Analisis Kesesuaian Tugas Teknologi Terhadap Dampak Kinerja Menggunakan Model Task Technology Fit Pada PT Pelindo III Cabang Tanjung Perak Surabaya - Nurdiwiyandra, Sidiq Arbingta; Hariadi, Bambang; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT. Pelindo III Branch Tanjung Perak Surabaya is one of the State-Owned Enterprises engaged in the port terminal operator services. In achieving the company's mission of making competent human resources, performing reliably, and noble-minded the company today will measure the extent to which support of applied information technology supports individual tasks so that the achievement of performance. Based on the facts given by PT. Pelindo III, the realization of the performance is only about 52% of the 85% target with several factors, namely data quality 23.50%, 8.70% operational pattern, 13.33% human resources and 6.00% %. To investigate the influence of task characteristic, technological characteristic to conformity of technology task, this research uses Task Technology Fit model which is a formal construct which is technology capability to support task in job.. The type of data used is the primary data obtained through the distribution of questionnaires.The result of this research is found that the characteristic of the task has significant effect on the conformity of technological tasks, the technological characteristic has no significant effect on the conformity of technological tasks and the suitability of technological tasks with significant impact on the performance impact